Menilik Cara Kreatif Penyampaian Pesan Iklan Persuasif pada Unggahan Instagram Transportasi Online - Angela, Rachel; Loisa, Riris (Koneksi, 2023)
The development of media makes advertising methods more varied because of every minute people are exposed to ads. Many ads are eventually neglected so that ads lose their main function, the persuasive function. Even so, there are still ads that interest the audience. The purpose of this study was to find out what persuasive communication approaches and techniques as well as advertising message execution style used by one of the largest online motorcycle taxi companies in promoting its main product. This study uses the theories and concepts of persuasive communication and advertising messages, descriptive quantitative approaches, and content analysis methods. The data collection method used are non-participatory observation, documentation, and literature study. The sample used was 17 advertising videos uploaded on Instagram account @gojekindonesia with a time range from January 2022 to September 2022. The results showed that the approach and technique used are an approach based on evidence, fear, humor, and diction, association techniques, integration, rewards, order, rationalization, and conformity. Then, the advertising message execution style applied are spokes person, demonstration, close up, story line, humor, slice of life, vignettes and situation, stop motion, rotoscope, brand name exposure, positive uniqueness, message source, message structure, transfer, slogan, glittering generalities, puns, product visual, product functions, headline and typography, testimonials, card stacking, and humor. Perkembangan media membuat cara beriklan harus semakin variatif karena setiap menitnya masyarakat diterpa oleh iklan. Banyak iklan yang akhirnya terabaikan sehingga iklan kehilangan fungsi utamanya, yaitu fungsi persuasif. Meskipun begitu, masih ada iklan yang menarik minat simak audiens. Tujuan penelitian ini adalah ingin mengetahui apa saja pendekatan dan teknik komunikasi persuasif serta gaya eksekusi pesan iklan yang digunakan oleh salah satu perusahaan terbesar ojek online dalam mempromosikan produk utamanya. Penelitian ini menggunakan teori dan konsep komunikasi persuasif dan pesan iklan, pendekatan kuantitatif deskriptif, serta metode analisis isi. Metode pengumpulan data yang digunakan, yaitu observasi non partisipatif, dokumentasi, dan studi pustaka. Sampel yang digunakan berjumlah 17 buah video iklan yang diunggah di akun Instagram @gojekindonesia dengan rentang waktu bulan Januari 2022 sampai bulan September 2022. Hasil penelitian ini, yaitu pendekatan dan teknik yang digunakan adalah pendekatan berdasarkan bukti, ketakutan, humor, dan diksi, teknik asosiasi, integrasi, ganjaran, tataan, rasionalisasi, serta konformitas. Lalu, gaya eksekusi pesan iklan yang diaplikasikan adalah spokes person, demonstrasi, close up, story line, humor, slice of life, vignettes and situation, stop motion, rotoscope, brand name exposure, positive uniqueness, message source, message structure, transfer, slogan, glittering generalities, plesetan, visual produk, fungsi produk, headline atau tipografi, testimonials, card stacking, dan humor.